Clinical features of heart failure in patients with atrial fibrillation: the role of the endovascular left atrial appendage closure - D. V. Pevzner; N. S. Kostritca; I. A. Merkulova; O. B. Dorogun; A. L. Komarov; I. S. Yavelov (Рациональная фармакотерапия в кардиологии, 2023)
Aim. To evaluate the long-term impact of endovascular left atrial appendage occlusion (LAAO) on heart failure (HF) course in patients with atrial fibrillation (AF).Materials and Methods: The prospective cohort study included patients with AF, HF, and a high risk of thromboembolic events, of which 39,6% underwent LAAO, 60,4% — received standard preventive therapy for cardioembolic events. Changes in BNP levels in the LAAO and control groups were analyzed throughout the observation period. The incidence of unfavorable HF outcomes (decompensated HF, hospitalizations related to HF, worsening HF class) was compared using the Cox-regression analysis with the log-rank test. A univariate analysis using Cox regression was conducted to identify independent predictors of endpoint achievement, involving all clinical and historical factors. Subsequently, a multivariate analysis was carried out, with predictors selected through the Wald exclusion test from those factors with a p-value less than 0.2 in the univariate analysis. Each factor was found to be a statistically significant independent predictor of the endpoint, with the overall model significance of p<0,001Results: s. The study included 139 patients (55 — LAAO group; 84 — control group) with a 3-year follow-up period. Most patients in the study had class I-III HF with preserved left ventricular ejection fraction (93,5%). In both groups, the level of BNP increased significantly over the observational period. Despite the initial differences between the groups, no differences were observed between the groups 1-3 years after the start of the study, which may indicate a tendency towards a lower growth rate of BNP in the LAAO group. The achievement rate of all endpoints was similar in both groups without significant differences. Multivariate analysis identified significant predictors of HF decompensation in the study cohort including left atrial volume, BNP levels, and HF class.Conclusion. Our study hasn’t shown any negative impact of endovascular LAAO on HF course in patients with AF. Additionally, several predictors of HF decompensation were identified in this patient cohort.